India policy forum - Shekhar Sha., Ed; borsworth, Barry., Ed; Karthik Muralidharan., Ed (sage, 2017)
The India Policy Forum (IPF) is India’s most prominent annual economic policy conference in the summer season of New Delhi and is organized by NCAER, the National Council of Applied Economic Research. The primary goal of the IPF is to promote original policy and empirical research on India, including policy-focused review articles that seek to define the best economic policy advice based on robust, empirical research. The annual IPF conference provides a unique combination of intense scholarship and expert commentary on commissioned research papers with a strong focus on policy. The revised papers and conference proceedings are published in this volume, including the comments of paper discussants and a summary of the floor discussion on each paper.